Нові та рідкісні для України види роду Leccinum (Boletales, Basidiomycota) - Гелюта, В.П.; Акулов, О.Ю. (Український ботанічний журнал, 2012)
В результате критического анализа установлено, что род Leccinum в Украине представлен 15
видами. Обычными являются L. aurantiacum, L. pseudoscabrum, L. scabrum и L. versipelle. К сравнительно редким (найдены до 15 раз) принадлежат L. crocipodium, L. duriusculum, L. holopus и L.
vulpinum, а L. albostipitatum, L. melaneum, L. palustre, L. piceinum, L. schistophilum и L. variicolor
находили по 1—3 раза. Как новые для Украины приводятся L. albostipitatum, L. melaneum, L.
palustre, L. piceinum и L. schistophilum. Оценка распространения L. rufum на основании литературных сведений не была возможной. As a result of critical study, 15 species of the Leccinum genus are reported for Ukraine. Leccinum aurantiacum,
L. pseudoscabrum, L. scabrum, and L. versipelle are found to be common species. Leccinum crocipodium,
L. duriusculum, L. holopus, and L. vulpinum have each up to 15 records. Leccinum albostipitatum, L.
melaneum, L. palustre, L. piceinum, L. schistophilum, and L. variicolor are very rare species (1—3 re cords in
the country). Leccinum albostipitatum, L. melaneum, L. palustre, L. piceinum, and L. schistophilum are new
for Ukraine species. Based on the literature data only, distribution of L. rufum is impossible to assess.